STUDY CASE OF TEMATIK LEARNING IN KINDERGARTEN CHILDREN AGES 4-6 YEARS WITH SCIENTIFIC APPROACH IN KINDERGARTEN KARTIKA IV PALEMBANG - RUKIYAH RUKIYAH (Sriwijaya University Learning and Education International Conference, 2016)
A study entitled Thematic Study case Learning Kindergarten (TK) byUsing Scientific Approach has been conducted in Children Ages 4-6 Years in TKKartika IV Palembang B. The aim of the study is to determine the planning,implementation, and evaluation, as well as the perception of teachers, andparents, principals of the thematic learning by using a scientific approach. Themethod used is descriptive qualitative method. Research conducted at TK KartikaIV Palembang. Subject of the study consisted of two kindergarten teachers in theclass B and 4-6 year olds amounted to 32, Headmaster, and parents . Technique tocollection the data is made by triangulation technique / combination ofobservation/participant observation, interviews and documentation. Thequestionnaire was also used to collect data from students's parents. The resultsshowed both the teacher is only one teacher who made learning plan in the formof Daily Activity Plan. Daily Activity Plan had been created using thematiclearning by using a scientific approach. Implementation of thematic learning byusing a scientific approach in both Class B, have not been implementedoptimally. Both teachers surveyed did not carry out an evaluation at the end of thelesson. Each teacher has a positive perception of the thematic learning by using ascientific approach, but still find it difficult to carry it out is not maximized. Theschool principal has to supervise the learning in several ways (observation,supervision and coaching). While parents do not feel satisfied with the result.